"Everyone needs a class like this": High school students' perspectives on a gay and lesbian literature course - Helmer, Kirsten (Educational Forum, 2015)
This article offers insights on how students experienced and made sense of their learning in a trimester-long high school Gay and Lesbian Literature course. Drawing on questionnaires and interviews that the students completed as part of a larger ethnographic study of this class, the author shows how a queer-themed literature curriculum is relevant for both LGBTQ-identifying and straight-identifying students and contributes to a better school climate.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; discipline; identités LGBTQIA2+; pédagogie; périodes historiques; ressource en ligne; régions géographiques; science de l'éducation; thématiques; école secondaire; états-unis

Queer inclusion in teacher education: Bridging theory, research, and practice - Murray, Olivia J. (Routledge, 2015)
Queer Inclusion in Teacher Education explores the challenges and promises of building queer inclusive pedagogy and curriculum into teacher education. Weaving together theory, research findings, and practical "how-to" strategies and materials, it fills an important gap by offering a clear roadmap and resources for influencing the knowledge, beliefs, and actions of faculty working with pre-service teachers. While the book has implications for policy change, most immediately, readers will feel empowered with ideas for faculty development they can implement in their own teacher education programs. Looking at both the politics and practices of teacher education and the ways in which queer issues manifest in schools, it is hopeful in suggesting that if teachers and pre-service teachers can critically reflect on homophobia and heteronormativity, they can begin to think about and relate to queer youth in a different, more positive and inclusive way. A Companion Website [http://queerinclusion.com] with additional activities and materials for teacher educators and faculty development and a practical guide enhances the usefulness of the book.
Keywords: LGBTQIA2+; approches et analyses; discipline; hétérosexisme; identités LGBTQIA2+; outils; ouvrages de références; pédagogie; pédagogie queer; queer; sciences de l'éducation; systèmes d'oppressions; systèmes éducatifs; thématiques

Pedagogy and content in sexuality education courses in US colleges and universities - Oswalt, Sara B.; Wagner, Laurie M.; Eastman-Mueller, Heather P.; Nevers, Joleen M. (Sex Education : Sexuality, Society and Learning, 2015)
Most research on sexuality courses in US higher education was conducted in the 1980s and 1990s. Less is known about what is being taught in undergraduate sexuality courses today; this study sought to fill that gap. Reviewing content based on 161 courses (provided by 150 different instructors) from all regions of the USA, this study examined overall descriptions of course content and pedagogical strategies in relation to the academic position of the instructor, region of the country and course enrolment size. Results indicated similar content and pedagogical strategies employed with limited differences based on demographic characteristics. The most commonly taught subjects were sexual orientation (95.0%), communication (93.8%), gender identity (93.2%) and gender roles (93.2%). Most courses included reference to contraception (89.4%), HIV and AIDS (88.2%) and STIs (85.7%). Some notable differences included the fact that tenured or tenure-track instructors were more likely to lecture compared to non-tenure-track instructors, and 100% of courses in the West and Northeast addressed sexual orientation compared to 96% for the Midwest and 85% for the South. Most courses included discussion of pleasure (91.1%) and incorporated sexually explicit content (61.9%). The benefits and challenges of having guidelines for sexuality courses at the university/college level were explored.
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; discipline; périodes historiques; ressource en ligne; régions géographiques; science de l'éducation; sexualité; systèmes éducatifs; thématiques; éducation sexuelle; états-unis; étude qualitative; étude quantitative